(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to determine the effect of affiliate marketing, live streaming, flash sales, and online customer reviews on purchasing decisions among users of the Tiktok Shp application. The population in this study were students of the Faculty of Creative Design and Digital Business, ITSNU Pekalongan. The sample used in this study used the purposive sampling method. The type of data used was primary data by means of a questionnaire. The analysis technique used was multiple linear regression analysis using SPSS version 30. The results of the study partially showed that: (1) Affiliate Marketing had a positive effect on purchasing decisions with a significance of 0.001 <0.05. (2) Live streaming had a positive effect on purchasing decisions with a significance of 0.024 <0.05. (3) Flash Sale had a positive effect on purchasing decisions with a significance of 0.001 <0.05. (4) Online Customer Reviews had a positive effect on purchasing decisions with a significance of 0.001 <0.05. Meanwhile, the simultaneous results show that Affiliate Marketing, live streaming, Flash Sale, and Online Customer Review have an effect on purchasing decisions with a significance of 0.001 <0.05. and an Adjusted R Square value of 0.637. This means that the variables Affiliate Marketing (X1), live streaming (X2), Flash Sale (X3), and Online Customer Review (X4) have an effect on purchasing decisions (Y) on TikTok Shop by 63.7%. While the remainder 36.3% is influenced by other variables outside this regression equation that are not studied